DUKUNGAN KELUARGA TENTANG TOILET TRAINING DENGAN KEBERHASILAN TOILETING PADA ANAK USIA 1 - 6 TAHUN DI PAUD AL HILAL KABUPATEN SUMENEP - Zakiyah Yasin; Nabela Alfina Aulia (Fakultas Ilmu Kesehatan, 2019)
In this era of globalization, parents can take care their toddler or pre – school children easily. Children at the toddler or pre – school age grow significantly. Parent supports is needed in guiding their children practicing the toilet training. Toilet training means children defecating and urinating control. Toilet training success is affected by parent knowledge, parents support, mother’s job, the quality of mother’s care, neighborhood and the availability of bathroom, soap, etc. This research uses descriptive method with cross sectional design. At this research uses all population that 30 families and 1 till 6 years old – children recorded at PAUD AL Hilal Sumenep Regency. This research uses premiere data being obtained from questionnaire filled by respondents. This study aims to determine Family support about toilet training according to 1 till 6 years old children toileting success at PAUD Al Hilal Sumenep Regency. The result show most of the respondents give good support (21 respondents or 70 %) and most the respondent’s children success in toileting (17 respondents or 56,67 %). The conclusion is most of the respondents give good support to the toileting success at PAUD Al Hilal Sumenep Regency. So do the children. Respondent can increase the family support to their children by giving attention if their children had time to do toilet training.